Novel water-use strategies of Colorado wetland plants: implications for wetland water loss - Wright, Anna, author; Ocheltree, Troy, advisor; Sueltenfuss, Jeremy, advisor; von Fischer, Joe, committee member (Colorado State University. Libraries, 2023)
In the arid west, there is a tension between wetland restoration and water rights. Wetlands, relied upon by humans and wildlife alike, also contribute significantly to evapotranspiration (ET) due to higher water tables and dense vegetation. It is therefore critical to understand how much water wetlands lose to evaporation and transpiration, and what affects wetland water loss. This paper quantifies the transpiration of five abundant wetland species and investigates physiological mechanisms that drive transpiration rates for each species. The focal species transpire significantly different amounts at the leaf-level and when scaled to ground area. Stomatal response to environmental stimuli differed from upland stomatal responses, which suggests that wetland plants prioritize carbon uptake over hydraulic safety and do not align with current paradigms for stomatal responses to vapor pressure deficit, leaf water potential, or turgor loss point. Understanding species' stomatal responses to extreme environmental conditions is key to managing this rare and critical ecosystem as the climate changes.
Keywords: stomatal conductance; turgor loss point; wetlands; transpiration; leaf water potential; water-use